PENERAPAN MODEL PEMBELAJARAN THINK ALOUD PAIR PROBLEM SOLVING (TAPPS) PADA MATERI PELUANG SISWA KELAS VIII MTS ASY SYAFI’IYAH GONDANG - Tsania Al'afifah (Program Studi Pendidikan Matematika UIN Raden Fatah Palembang, 2018)
This research aim to obtain a description about applying Think Aloud Pair problem Solving (TAPPS) learning model, mathematical communication ability and learning outcome on mathematical learning in class VIII MTs Asy Syafi’iyah Gondang. This was a qualitative research which refers to the design of the research Miles and Huberman that is data collection, data reduction, data display and conclusion drawing. Data collection technique used is interview, test and documentation. The research results showed that applying of Think Aloud Pair Problem Solving (TAPPS) learning model goes well, student can understanding provided content easily, and student learning outcome is better than before. On the strength of mathematical communication ability indicators, student with high mathematical communication ability can get all indicators given. Student with moderate mathematical communication ability difficulty reaching third indicator. And student with low mathematical communication ability difficulty reaching second and third indicators.